2021
DOI: 10.1007/s10811-021-02655-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinase-aided amplification combined with lateral flow dipstick for the rapid detection of Amphidinium carterae

Abstract: In the context of global climate change, the frequency and duration of harmful algal blooms (HABs) due to eutrophic coastal waters have increased. HABs can cause marine ecological imbalance, massive socio-economic damage, and potential public health problems. Therefore, accurate and specific techniques that can rapidly detect harmful algae are critical to expedite early monitoring and prediction of HABs. Although some methods based on amplification have previously been described, limitations associated with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…However, cryptic species cannot always be resolved with these genes, and more variable regions, such as the ITS regions, may be more appropriate. The ITS sequence was chosen as the target sequence of qPCR, RAA-LFD, LAMP-LFD, and RPA-LFD, as it is an effective molecular marker that is capable of detecting various HAB species accurately [26,27,49]. The choice of appropriate target sequences is essential for a molecular detection approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cryptic species cannot always be resolved with these genes, and more variable regions, such as the ITS regions, may be more appropriate. The ITS sequence was chosen as the target sequence of qPCR, RAA-LFD, LAMP-LFD, and RPA-LFD, as it is an effective molecular marker that is capable of detecting various HAB species accurately [26,27,49]. The choice of appropriate target sequences is essential for a molecular detection approach.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the expertise and time that are required for the microscopic discrimination of species, molecular methods that monitor the environmental concentrations of Pseudonitzschia provide a rapid alternative for early bloom detection and toxin accumulation prediction. The main molecular detection methods for HAB species have included polymerase chain reaction (PCR) [18], quantitative PCR (qPCR) [19][20][21], enzyme-linked immunosorbent assay [22], rolling circle amplification [23], helicase-dependent amplification [24], nucleic acid sequence-based amplification [25], loop-mediated isothermal amplification (LAMP) [26], recombinase-aided amplification (RAA) [27], and recombinase polymerase amplification (RPA) [28], among others [29]. Currently, the detection of P. multiseries is mainly divided into two categories.…”
Section: Introductionmentioning
confidence: 99%
“…RAA-LFT has the same technical advantages as RPA-LFT. Another very attractive advantage of RAA-LFT is that its cost is much lower than that of RPA-LFT, which is ideal for the batch testing of samples [44].…”
Section: Raa-lft Detection Of Plant Virusesmentioning
confidence: 99%
“…Of the ten paper-based RAA articles incorporated in this review, all reported paper-based detection but did not show paper-based extraction or amplification. Nine articles reported colorimetric detection using tagged probes/primers and AuNPs [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. For example, Xu et al used LFIA to detect Amphidinium carterae by implementing a species-specific primer tagged with biotin and a probe labeled with FAM [ 62 ].…”
Section: Raa and Mira With Paper Microfluidicsmentioning
confidence: 99%
“…Nine articles reported colorimetric detection using tagged probes/primers and AuNPs [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. For example, Xu et al used LFIA to detect Amphidinium carterae by implementing a species-specific primer tagged with biotin and a probe labeled with FAM [ 62 ]. In a few cases, Cas12a reporter probes and AuNPs were implemented for detection [ 65 , 66 ].…”
Section: Raa and Mira With Paper Microfluidicsmentioning
confidence: 99%